Pengaruh Topografi dan Umur Ayam yang Berbeda terhadap Berat Telur dan Haugh Unit Ayam Ras Petelur - Wijaksono, Tri Widi; Munir, Munir; Rasbawati, Rasbawati (Fakultas MIPA UNM, 2019)
Abstract. This study aims to determine the effect of topography and age of different breeds of chickens on egg weight and haugh unit. The study was conducted in August 2018, data collection was taken from Keluragan Amparita, Telulimpoe District, Sidenreng Rappang Regency, Mario Village Kulo District, Sidenreng Rappang Regency and Kaluppang Village, Maiwa District, Enrekang District. The study used 135 eggs as eggs. The study used a Factorial Randomized Block Design with three stages of treatment and three repetitions, namely Factor A (Age of chicken 30 weeks, age of chicken 50 weeks, and age of chicken 70 weeks) then Factor B (Topography of lowland, medium and high). The treatment of topographic influence and age of laying chicken showed that the effect of topography had a very significant effect (P <0.01) on egg weight while chicken age did not significantly affect egg weight (P> 0.05). Topography has a very significant effect on Haugh Unit (P <0.01), and chicken age has a significant effect (P <0.05) on Haugh units.Keywords: Laying Chicken, Topography, Egg Weight, Haugh Unit, and Chicken Age